Effects of body weight-supported Tai Chi Yunshou training on upper limb motor function in stroke patients: A three-arm parallel randomized controlled trial - Liying Zhang; Xiaoming Yu; Wangsheng Liao; Jiening Wang; Yan Lu; Naizhen Wang; Zhou Huanxia (PLoS ONE, 2025)
Objectives To form a unique body weight support-Tai Chi Yunshou (BWS-TCY) training method, apply it to the treatment of upper limb dysfunction after stroke, and provide a new safe and effective treatment method for the clinic. Methods A total of 93 subjects were recruited and randomly divided into conventional rehabilitation treatment (CRT) group, BWS-TCY group and traditional robot-assisted training (RAT) group in equal proportions. Subjects in the CRT group received 60 minutes of CRT daily. Subjects in the BWS-TCY group received 30 minutes of CRT and 30 minutes of BWS-TCY. Subjects in the RAT group received 30 minutes of CRT and 30 minutes of RAT. All interventions were conducted 5 days per week for 12 weeks. Outcome assessments included the Fugl-Meyer Upper Extremity Motor Function Assessment (FMA-UE), Wolf Motor Function Test (WMFT), absolute angular error (AAE), joint range of motion (JMA), modified Barthel Index (MBI), and stroke-related quality of life. Table (SS-QOL). Outcome measures were assessed at baseline, 4 weeks, 8 weeks, and 12 weeks later, and statistical analyzes were performed using two-way repeated measures analysis of variance. Results After 12 weeks of intervention, significant improvements were observed in all evaluation indicators for the three groups of subjects compared to before the intervention. The upper limb motor function (FMA-UE and WMFT) and proprioception (AAE) showed time effects, time × group interaction effects, and group effects. When comparing the groups, the FMA-UE in the BWS-TCY group, as well as the WMFT and MBI, showed statistically significant differences compared to the CRT group (P<0.05), but not statistically significant compared to the RAT group (P>0.05). The AAE of the BWS-TCY group showed no statistical difference (P>0.05) when compared to the CRT group and RAT group. Furthermore, a time effect was observed on the rotation direction (P<0.05), and pairwise comparison between groups revealed that the BWS-TCY group performed better than both the CRT group and the RAT group. After 12 weeks of intervention, there were time effects and interaction effects between BWS-TCY and daily living activities (MBI) and quality of life (SS-QOL), but no group effect was observed. There was no statistical difference between the two groups in SS-QOL. However, there was a statistical difference (P<0.01) in MBI between the two groups. Conclusions The 12-week BWS-TCY intervention has been shown to effectively improve upper limb motor function. Trial registration Retrospectively registered at chictr.org.cn on August 31, 2022 [ChiCTR2200063150] https://www.chictr.org.cn/showproj.html?proj=176229.